The relationship between the heart rate deflection point test and maximal lactate steady state - De Assis Pereira, P. E.; Piubelli Carrara, V. K.; Mello Rissato, G.; Pereira Duarte, J. M.; Fernandes Guerra, R. L.; Silva Marques, D. E.; Azevedo, P. H. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of this study was to investigate the use of the Heart Rate Deflection Point Test (HRDP) in the determination of the velocity at the Maximal Lactate Steady State (MLSS).